Parental beliefs and the influence of formal and informal literacy environments on preschoolers’ attitudes toward English learning - Qingyun Li; Kimberley Kong; Qian Li; Qian Wang (PLoS ONE, 2025)
English learning among Chinese preschoolers has increased in recent years. Despite policies that strongly oppose external English instruction for this age group, many parents are unrelenting and persist in providing English learning opportunities for their children. This study seeks to address how formal and informal literacy activities within the Home Literacy Environment (HLE) mediate the relationship between parental beliefs and Chinese children’s attitudes towards learning English in a foreign language context. Specifically, it explores: (1) how formal literacy activities within the HLE mediate this relationship, (2) how informal literacy activities within the HLE mediate this relationship. The study involved 405 participants who completed a questionnaire on family demographics, beliefs about the importance of early English education, the HLE, and children’s attitudes towards English learning. Quantitative data were analyzed using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach. Parental beliefs positively influence children’s attitudes towards English through formal and informal learning. These results highlight the importance of fostering a supportive and engaging HLE to enhance children’s positive attitudes towards learning English. The implications suggest that policy and practice should recognize the value of various literacy activities in early childhood education, particularly in the context of a foreign language and academically focused Asian society.